Introduction: Paper, Metal, Glass: Materials and Their Meaning in Pre-Modern Science - Reinhart, Katherine M. (Centaurus, 2024)
Abstract This special issue explores the materiality of science in the early modern period. The articles in this issue track the materials and objects of natural philosophical practice and question how they were made, copied, reused, and circulated during the process of creating scientific and artisanal knowledge. This issue further examines how both quotidian and rare materials, such as metal, glass, paper, or gemstones, often played a crucial role in these processes, as they were formed and transformed into objects of knowledge themselves. By considering the material meaning and contexts of these objects, this issue reveals the critical role that materials played in diverse forms of knowledge production and transfer in early modernity.
Keywords: Early Modern Science